ANALYSIS OF THE EFFECT OF AICC PARAMETERS VARIATION ON CNC MILLING MACHINES ON MACHINING TIME AND WORKPIECE ACCURACY - Sijabat, Henri Hendrik; Dharmajati, R Ariosuko (Jurnal Teknik Mesin (Journal Of Mechanical Engineering), 2024)
The global market for Computer Numerical Control (CNC) milling machines continues to grow at a significant rate, with the automotive industry being the largest end-user. The Fanuc 31i controller is one of the leading controllers in the manufacturing industry. This controller has AI nano CNC features that support high-precision movements and high-speed NC program execution. The more understanding of the AICC (AI Contour Control) parameter settings can make a significant contribution to improvement of production efficiency and quality. This research is conducted to investigate the influence of changing the "R" value in the AICC parameter on the CNC Milling machine OKK VP1200 with the Fanuc 31i controller to machining time and workpiece accuracy. The experiments were conducted on three shapes: complex, circle, and  square, using three test specimens with variations in AICC parameters ranging from R1 to R10. By adjusting these parameters, the actual machining time was recorded, and the accuracy of the machining process was measured using a Coordinate Measuring Machine (CMM) and later the data was analyzed. This study presents data and instructions for the application of AICC R1-R10 parameters that is adjusted to the specified tolerances or deviations. Furthermore, the research can provide the percentage of actual time compared to the programmed time if a CAM Programmer has determined the tolerance range limit or deviation of a product and determined which AICC parameters to use. In practice, a CAM Programmer can make predictions for two aspects based on the data in this research that are actual machining time and product accuracy.